2019
DOI: 10.14740/jh522
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia C: A Case Report With Updates on Diagnosis and Management of a Rare Bleeding Disorder

Abstract: Hemophilia C or factor XI deficiency is a rare clotting disorder with prevalence of only 1 per 1 million. A 24-year-old male with multiple abdominal surgeries complicated by wound infections and poor healing was admitted to plastic surgery service for an elective abdominoplasty. Hematology was consulted for increased intraoperative and postoperative bleeding. Laboratory workup showed high-normal activated plasma thromboplastin time of 31 s (reference: 23-34 s), prothrombin time (PT) of 15 s (reference: 11.8-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The use of antifibrinolytic medication may help improve overall hemostasis[ 14 ]. For major procedures in individuals with severe FXI deficiency or with a significant bleeding phenotype, prophylactic replenishment using FXI concentrates or FFP is recommended in the preoperative period[ 1 ]. FXI concentrate has been associated with a higher thrombotic risk than FFP[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antifibrinolytic medication may help improve overall hemostasis[ 14 ]. For major procedures in individuals with severe FXI deficiency or with a significant bleeding phenotype, prophylactic replenishment using FXI concentrates or FFP is recommended in the preoperative period[ 1 ]. FXI concentrate has been associated with a higher thrombotic risk than FFP[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia C, or factor XI (FXI) deficiency, is a rare autosomal coagulation disorder[ 1 ]. Patients may be asymptomatic until they are hemodynamically challenged following trauma or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, FXI complexes with high molecular weight kininogen to maintain its stability in circulation (half-life ≈ 52 h) and facilitate binding to negatively charged molecules that promote its activation to FXIa . Although the intrinsic pathway amplifies clot propagation, it is less likely that FXI contributes to hemostasis. , In patients with FXI deficiency, it has been reported that spontaneous bleeding is rarely observed, but the bleeding risk is increased following injuries and surgeries. More recently, a large retrospective cohort study confirmed that FXI deficiency (FXI activity < 50%) was associated with an increased risk of severe bleeding and clinically relevant nonsevere bleeding, primarily postprocedure . This phenotype is unlike the more frequent spontaneous bleeding found in patients with hemophilia A (factor VIII deficiency) and hemophilia B (factor IX deficiency), , supporting a minor role of FXI in hemostasis.…”
Section: Role Of Factor XI (Fxi) In Thrombosis and Hemostasismentioning
confidence: 99%
“…Factor VII deficiency and factor XI deficiency (hemophilia C or Rosenthal syndrome) are rare bleeding disorders associated with variable phenotypes ranging from asymptomatic cases to severe bleeding. 1 , 2 , 3 , 4 , 5 , 6 Hemostasis starts with formation of the platelet plug, followed by the clotting factor cascade resulting in thrombin generation and fibrin clot formation. The extrinsic and intrinsic pathways work synergistically to generate factor X and thrombin.…”
Section: Introductionmentioning
confidence: 99%